Electromagnetic Field Associated With Dermoscope Magnets May Affect the Safety of Cardiac Implanted Electronic Devices Patients - Sławiński, Grzegorz; Sławińska, Martyna; Usarek, Zbigniew; Sobjanek, Michał; Kempa, Maciej; Liżewska-Springer, Aleksandra; Lewicka, Ewa; Nowicki, Roman J.; Raczak, Grzegorz (Frontiers in Cardiovascular Medicine, 2021)
Dermoscopy is currently used as an auxiliary tool in general dermatology. Since some commercially available dermoscopes have built-in magnets, electromagnetic interference (EMI) may occur when examining cardiac implantable electronic devices (CIED) patients. The aim of the study was to create maps of electromagnetic fields defining a safe distance in terms of EMI. The study was performed in laboratory conditions using measuring equipment specially designed for this purpose. The following dermoscopes have been tested: Illuco IDS-1100, Visiomed Luminis, Visiomed Luminis 2, Heine NC2 with and without a contact plate, DermLite DL4, and DermLite Handyscope. Measurements were made for the following set of lift-off distances: 5, 10, 20, 30, 40, 50, and 150 mm. Each 2D scan consisted of 10-line scans shifted from each other by 10 mm. The strength of the magnetic field decreased with the distance from the faceplate. The distribution of the magnetic field differed depending on the position of the magnets. The highest magnetic field was recorded in the center of the Heine NC2 faceplate (up to 8 mT). In most cases, at a distance of 10 mm, the magnetic field strength was measured below 1 mT, with the exception of Heine NC2 and Heine NC2 with a contact plate. All tested dermoscopes generated a magnetic field of <1 mT at the distance of 20 mm. The use of dermoscopes with built-in magnets may affect the functioning of CIEDs, and the impact may vary depending on the type of dermoscope.